A framework to specify agent-based models in geographic sciences - Grueau, Cédric (2017)
Agent-Based Modeling (ABM) and simulation have gained popularity in the Geographic Information Systems (GIS) domain. Despite the increasing number of models built by experts and users, it remains challenging for users to specify their models in a manner in which one can understand it. This constraint represents an inhibition to the development and acceptance of the ABM approach. In this paper, we raise the questions that need to be answered in order to cope with ABM specification issues. We review some of the existing solutions that have been developed. We propose a framework that includes a domain specific modeling language to respond to ABM specification problem. We finally present the first step towards its development.